The effect of pre-exercise Nordic hamstring exercise on hamstring neuromuscular response during soccer-specific activity - O'Boyle, M.; Brogden, C. M.; Greig, M. (Science and Medicine in Football, 2021)
Background: The Nordic hamstring exercise (NHE) has emerged as a popular intervention for improving eccentric hamstring strength, however recent literature suggests there is a potential for an increase in injury risk during subsequent exercise. Methods: To quantify the influence of pre-exercise NHE on the electromyographical response of the hamstrings, 10 male soccer players completed an experimental trial comprising 6 sets x 5 repetitions of NHE prior to the completion of a 45 minute soccer-specific protocol. Post-exercise NHE were performed in the experimental and control (no pre-exercise NHE) trials. Electromyographic (EMG) response (integrated, mean and peak amplitude) of the biceps femoris to the pre- and post-exercise NHE and the soccerspecific exercise protocol was quantified. Results: Integrated (P= 0.025) and mean (P= 0.020) EMG elicited a significant main effect for time in the soccer-specific protocol with higher values during the first 15 mins indicative of a fatigue effect. However, there was no trial x time interaction (P = 0.78). There was no difference between trials in the EMG response to pre-exercise (P= 0.30) or post-exercise (P= 0.16) NHE trials. Conclusions: Therefore, although previous studies suggest performing pre-exercise NHE might impair maximal strength metrics, the current study`s results suggest that it does not impair the electromyographical response to subsequent soccer-specific exercise or NHE repetitions.